FEATURES OF THE METABOLISM OF NITRIC OXIDE IN PERIODONTAL DISEASES IN PATIENTS WITH COPD IN COMBINATION WITH CHD - Emelyanova, N.Yu.; Galchinskaya, V.Yu.; Bondar, T.N. (World of Medicine and Biology, 2018)
The paper considered the role of nitric oxide in the pathology of periodontal tissues in patients with chronic obstructive pulmonary disease (COPD) in combination with coronary heart disease (CHD). It was found that in the blood plasma there was a decrease of total level of stable metabolites in patients with COPD as compared to the control group, as well as a significant increase of expression of inducible NO synthase in the materials the gingival mucosa.